Genome Characterization of a Novel Wastewater Bacteroides fragilis Bacteriophage (vB_BfrS_23) and its Host GB124 - Tariq, Mohammad A.; Newberry, Fiona; Haagmans, Rik; Booth, Catherine; Wileman, Tom; Hoyles, Lesley; Clokie, Martha R. J.; Ebdon, James; Carding, Simon R. (Frontiers in Microbiology, 2020)
Bacteroides spp. are part of the human intestinal microbiota but can under some circumstances become clinical pathogens. Bacteroides fragilis is the most commonly isolated anaerobic pathogen from this genus and is the only Bacteroides spp. that has been shown to induce abscess formation without other bacteria being involved. Phages are a potentially valuable therapeutic treatment option for many pathogens, but phage therapy for pathogenic Bacteroides spp. including B. fragilis is currently limited by a lack of characterised, genome-sequenced phages. Here we describe the isolation from sewage wastewater and genome of a lytic phage, vB_BfrS_23, that infects and kills B. fragilis strain GB124. Transmission electron microscopy identified this phage as a member of the Siphoviridae family. The phage is stable when held at temperatures of 4 °C and 45 °C for 1 hour. It has a very narrow host range, only infecting one host from a panel of B. fragilis strains (n=8). Whole-genome sequence analyses of vB_BfrS_23 determined it comprised double-stranded DNA phage and is circularly permuted, with a genome of 48,011 bp. The genome encodes 73 putative open reading frames. We also sequenced the host bacterium, B. fragilis GB124 (5.1 Mb), which has two plasmids of 43,923 bp and 4,138 bp. Although this phage is specific, it’s isolation together with the detailed characterisation of the host B. fragilis GB124 featured in this study represent a useful starting point from which to facilitate the future development of highly-specific therapeutic agents. Furthermore, the phage could be a novel tool in determining water (and water reuse) treatment efficacy, and for identifying human faecal transmission pathways within contaminated environmental waters and foodstuffs.